USING SOME STRATEGIES IN SIMULTANEOUS INTERPRETING (Konferensiyalar | Conferences, 2024)
The article investigates the strategies which are used by the translators in simultaneous interpretation. Majority of the interpretation researchers consider the translation strategies as an important tool while translating from the source language to the target language. In simultaneous translation, the interpreter utilizes a number of strategies. It generally depends on the situation. It was also recommended that linguistic and extra-linguistic factors affect this state.Strategies also serve as a vital tool for interpreters in navigating the complexities of simultaneous translation.